ALLOCATIVE EFFICIENCY OF RESOURCE UTILIZATION IN FISH FARMING IN OWO LOCAL GOVERNMENT AREA OF ONDO STATE, NIGERIA. - Abbas, Asiru Monday (Innovare Journal of Agricultural Sciences, 2018)
The study assessed resource-use efficiency among fish farmers in Owo Local Government Area of Ondo State, Nigeria. A multi stage sampling technique was used to select 50 fish farmers for the study. Data obtained were analyzed using multiple regression analysis. Significant determinants of the quantity of fish harvested at the end of the production cycle were fish seeds (0.647) and the quantity of feeds used (0.339). The two productive resources were significant at 0.01 probability level. The values of allocative efficiency of all the inputs used indicated that pond size (7.041) and fish seeds (11.500) were under-utilized while labour (0.705) was over-utilized; only feeds (1.032) were optimally utilized during fish production process. Under-utilized resources should be optimally used in order to obtain the best possible output. Excessive use of labour should be reduced so as to cut cost of production and increase profit margin. It is also recommended that fish farmer's capacity should be developed through regular training on how to allocate productive resources efficiently.